Strategi Komunikasi Pembangunan dalam Difusi Teknologi Pengolahan Limbah Air (Studi Kasus IPAL Dusun Giriharja dan Biotoilet SDN Babakan Sinyar) - Anton Surahmat; Rufi Rismayanti (Jurnal Komunikasi Pembangunan, 2022)
Wastewater has great potential to be a valuable resource for society. In both developed and developing countries, the issue of wastewater recycling has always been an important topic. This is because wastewater contains many substances which if properly treated can provide various benefits, such as reducing environmental pollution, organic fertilizers, and renewable energy sources. This study aims to describe how the communication strategy for the development of the Research Center for Environmental and Clean Technology (PRLTB BRIN) to diffuse wastewater treatment technology in Sumedang Regency and Bandung City, Indonesia. This study uses an In-depth interview, literature studies, and observations were conducted to analyse how the communication strategy and the stages of innovation diffusion took place. The results showed that the diffusion of the Biogas WWTP technology innovation went well until the confirmation stage. The participatory strategy with interpersonal communication channels is the main basis for the application of Biogas WWTP technology. Meanwhile, the learning design strategy with interpersonal communication strengthened the compost toilet trial at SDN 210 Babakan Sinyar. The diffusion stage of the compost toilet innovation at SDN 210 Babakan Sinyar is still at the decision stage.